Pengaruh Strategi Relationship Marketing Terhadap Brand Iphone Dengan Electronic Word Of Mouth Sebagai Variabel Mediasi Pada Generasi Z - Kamila Asadiyah Azahro; Erwinda Sam Anafih (STIE AUB Surakarta, 2026)
This study aims to analyze the effect of relationship marketing on brand resonance for the iPhone brand, with electronic word of mouth serving as the mediating variable Generation Z consumers in Indonesia. In this era of rapid digital transformation, technology companies face the need to forge strong emotional bonds with the digital consumer generation. This study employed a quantitative method involving 195 respondents from the Greater Solo area, who were selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings show that relationship marketing significantly influences the creation of brand resonance and serves as a driver of electronic word of mouth. However, an interesting result shows that electronic word of mouth does not significantly influence brand resonance for high-equity brands such as the iPhone among Generation Z, nor does it prove to be a mediator. This fact underscores that for global premium brands, users’ direct experiences and personal relationships with the company play a far more dominant role in building brand attachment than digital opinions from fellow consumers on social media platforms.